2017
DOI: 10.3344/kjp.2017.30.2.134
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of intrathecal versus intra-articular dexmedetomidine as an adjuvant to bupivacaine on postoperative pain following knee arthroscopy: a randomized clinical trial

Abstract: BackgroundPostoperative pain is a common, distressing symptom following arthroscopic knee surgery. The aim of this study was to compare the potential analgesic effect of dexmedetomidine after intrathecal versus intra-articular administration following arthroscopic knee surgery.MethodsNinety patients undergoing unilateral elective arthroscopic knee surgery were randomly assigned into three groups in a double-blind placebo controlled study. The intrathecal dexmedetomidine group (IT) received an intrathecal block… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…21,22 Opioid- attributed to the relatively small dose used and the poorly vascular articular surface. 5 Ismail et al 28 recruited 90 patients undergoing unilateral elective knee arthroscopy and concluded that IA was superior to intrathecally administered dexmedetomidine due to prolonged analgesia (413 ± 34 min) in the IA group compared with 359 ± 30 and 224 ± 36 min in the intrathecal and control groups respectively, in addition to 24 h less analgesic consumption than the other groups.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…21,22 Opioid- attributed to the relatively small dose used and the poorly vascular articular surface. 5 Ismail et al 28 recruited 90 patients undergoing unilateral elective knee arthroscopy and concluded that IA was superior to intrathecally administered dexmedetomidine due to prolonged analgesia (413 ± 34 min) in the IA group compared with 359 ± 30 and 224 ± 36 min in the intrathecal and control groups respectively, in addition to 24 h less analgesic consumption than the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Metwalli et al 5 concluded that IA dexmedetomidine alone provided around 312 min mean time of postoperative analgesia after knee arthroscopy. No systemic side effects were observed in any of the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations